The Effect of Local Area Crime on Mental Health - Christian Dustmann; Francesco Fasani (Institute for the Study of Labor (IZA), 2013)
This paper analyses the effect of local crime rates on the mental well-being of residents. Our identification strategy addresses the problem of sorting, and endogenous moving behaviour. We find that crime causes considerable mental distress of residents, and that these effects are mainly driven by property crime. However, individuals react also to violent crime, in particular in areas individuals may be exposed to when following their daily routines, such as travel to work. Local crime creates more distress for females, and is mainly related to depression and anxiety. The impact on mental well-being is large: We find that the increase in mental distress following a one standard deviation increase in local crime is about 2-4 times as large as that caused by a one standard deviation decrease in local employment, and about one seventh of the effect experienced by in the direct aftermath of the London Bombings of Jul 7th, 2005.
Keywords: I18; K42; R23; 330; neighbourhood effects; mental wellbeing; fear of crime